Job Satisfaction Mediates How Management Information Systems and Work Professionalism Shape Employee Performance in West Nusa Tenggara’s Industry Department - Putri Ainayah Alfatihah; Thatok Asmony; Waraporn Jirachiefpattana (Tinta Emas Publisher, 2025)
This study aims to analyze and prove the influence of management information systems and work professionalism on employee performance with job satisfaction as an intervening variable at the West Nusa Tenggara (NTB) Provincial Industrial Office. This study uses a quantitative approach involving 50 respondents as a sample. Data were collected through questionnaires and analyzed using the SmartPLS 4.0 analysis tool. The results show that management information systems have a significant effect on job satisfaction, work professionalism has a significant effect on job satisfaction, management information systems have a significant effect on employee performance, and work professionalism has a significant effect on employee performance. However, job satisfaction does not have a significant effect on employee performance. This finding implies that improving management information systems and work professionalism can directly improve employee performance, although job satisfaction is not a determining factor in improving performance. This study contributes to understanding the dynamics of factors that influence employee performance in the public sector, especially in the NTB Provincial Industrial Office.